2018
DOI: 10.1177/0042085918801433
|View full text |Cite
|
Sign up to set email alerts
|

School Punishment and Education: Racial/Ethnic Disparities With Grade Retention and the Role of Urbanicity

Abstract: There are racial/ethnic disparities associated with school punishment practices and academic progress. In addition, research suggests that urban schools have stricter school punishment practices and higher grade retention rates. What remains unknown, however, is the relationship between race/ethnicity, school punishment practices, and retention rates across urban, rural, and suburban schools. Thus, this study draws from the Texas Education Agency’s Public Education Information Management System and Critical Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Previous research has demonstrated that suspensions are inequitably distributed according to social and demographic characteristics, such as race and ethnicity, and that these inequitable distributions—often referred to as “punishment gaps”—can eventually lead to “achievement gaps” (Morris & Perry, 2016). While schools are often segregated along these social and demographic lines, only recently has research begun to explore the impacts of this inequitable distribution of suspensions at the school-level (see Peguero et al, 2018).…”
Section: Literature Review: High-suspension Schoolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that suspensions are inequitably distributed according to social and demographic characteristics, such as race and ethnicity, and that these inequitable distributions—often referred to as “punishment gaps”—can eventually lead to “achievement gaps” (Morris & Perry, 2016). While schools are often segregated along these social and demographic lines, only recently has research begun to explore the impacts of this inequitable distribution of suspensions at the school-level (see Peguero et al, 2018).…”
Section: Literature Review: High-suspension Schoolsmentioning
confidence: 99%
“…At the same time, many schools have adopted an authoritarian approach to discipline, relying heavily on exclusionary practices, such as suspensions. These approaches may be especially prevalent in urban communities, which “have often been characterized by social isolation, heightened police surveillance, perceived family dysfunction, high rates of unemployment and poverty, high rates of violent crime, and overcrowded and underfunded schools” (Peguero et al, 2018, p. 7). As a result of these exclusionary practices, many students have been pushed closer toward the criminal justice system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, schools that are urban (Shedd, 2015), Southern (Smith & Harper, 2015), charter (Losen, Keith, Hodson, & Martinez, 2016), “no-excuse” (Golann, 2015), large (Stewart, 2003), low achieving (Skiba et al, 2014), and have fewer teachers of color (Lindsay & Hart, 2017) tend to rely more heavily on punitive discipline. As most of these dimensions characterize the schools that Black and Latinx students attend, and do not fully account for racial disparities once they are considered (Peguero, Varela, Marchbanks, Blake, & Eason, 2018; Skiba et al, 2014), one could conclude that they merely proxy the pervasiveness of racial disparity in discipline. In sum, between-school variation in racial segregation leads to pronounced racial disparities in discipline, and the pervasiveness of segregation makes it difficult for parents to access less segregated schools where hyper-discipline could be less common.…”
Section: Policy Variation Between Schoolsmentioning
confidence: 99%
“…Just as increased social control in the criminal justice system is likely to affect defendants of color, increased surveillance, control, and punishment are likely to impact students of color disproportionately. Furthermore, the far-reaching consequences of severe school punishment—for instance, academic failure, arrest, gang involvement, and other negative life outcomes—underscore the need for continued investigations around what factors are associated with the continued creep of the culture of control into American schools (Peguero et al, 2021; Pesta, 2018; Widdowson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%